The labyrinth index - Stross, Charles (Stross, Charles. Laundry files novel., 2018)
"The arrival of vast, alien, inhuman intelligences reshaped the landscape fo human affairs across the world, and the United Kingdom is no exception. Things have changed in Britain since the dread elder god Nyarlathotep ascended to the rank of Prime Minister. Mhari Murphy, recently elevated to the House of Lords and head of the Lords Select Committee on Sanguinary Affairs (think vampires), finds herself in direct consultation with the creeping chaos, who directs her to lead a team of disgraced Laundry personnel into the dark heart of America. It seems the Creeping Chaos is concerned about foreign relations. A thousand-mile-wild storm system has blanketed the midwest, and the President is nowhere to be found. In fact, for reasons unknown the people of America are forgetting that the executive branch ever existed. The government has been infiltrated by the shadowy Black Chamber, and the Pentagon and NASA have been refocused on the problem of summoning Cthulhu. Somewhere, the Secret Service battle to stay awake, to remind the President who he is, and to stay one step ahead of the vampiric dragnet that's searching for him" --